Elders' health and wellbeing in elders' homes in Sri Lanka: An exploratory study - Dissanayake, L.; Weeratunga, M.K. (University of Colombo, Sri Lanka., 2019)
This study is the first national level investigation regarding care homes in Sri Lanka. It combines quantitative and qualitative approaches to give an extraordinary insight into the challenges faced by care homes.
Keywords: ageing, aged care indutry, community solutions, elders' homes, health and wellbeing